PENGARUH ASIMETRI INFORMASI, INSENTIF PAJAK, DAN RISIKO LITIGASI TERHADAP PRUDENCE AKUNTANSI (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR TEKNOLOGI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022) - Amalia, Rani; Mansur, Fitrini; Hernando, Riski (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to determine the influence of information asymmetry, tax incentives, and litigation risk on accounting prudence. The independent variables used in this research are information asymmetry, tax incentives, and litigation risk. Meanwhile, the dependent variable in the research is accounting prudence. This type of research is quantitative research. The population in the research is technology sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sample in this research was taken using a purposive sampling method with a total sample of 18 companies. The data analysis used in this research is multiple linear regression analysis with the help of the IBM SPSS version 26 program. The data in this research is secondary data obtained from the official website of the Indonesian Stock Exchange. The results of this research show that information asymmetry, tax incentives and litigation risk simultaneously influence accounting prudence. Partially, tax incentives have an effect on accounting prudence. Partially, information asymmetry and litigation risk have no effect on accounting prudence.